" Approaching a low carbon metropolis " A study of urban transformations based on rapid transit projects in Greater Cairo. Issue 1 (1st December 2022) - Al-Ashwal, Bakr Hashem Paumey
Abstract: Metropolis Cities play an essential role in climate crises: they are the main sources of carbon monoxide and carbon dioxide emissions. They differ from rural communities in that they are communities in which different aspects of the global climate crisis overlap. And since there is an urgent and urgent need for strong interventions by city planners in order to confront these climate changes. These cities need innovative ways and systems for their planning and management in effort to reduce its carbon footprint and adjust to climate change. A number of measures and approaches have been taken to confront the climate change crisis, but are these approaches and measures sufficient to achieve the radical transformation that our cities need. This research paper discusses an overview of the efforts of some major cities to confront climate change in order to bring about a sustainable transformation. Is the shift towards sustainable smart transport with its various systems sufficient to confront climate changes in Greater Cairo, or do we need plans that are all integrated together to achieve indicators of city sustainability?